2020
DOI: 10.1021/acschemneuro.0c00427
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation Mechanisms and Phytotherapeutic Intervention: A Systematic Review

Abstract: Neuroinflammation is indicated in the pathogenesis of several acute and chronic neurological disorders. Acute lesions in the brain parenchyma induce intense and highly complex neuroinflammatory reactions with similar mechanisms among various disease prototypes. Microglial cells in the CNS sense tissue damage and initiate inflammatory responses. The cellular and humoral constituents of the neuroinflammatory reaction to brain injury contribute significantly to secondary brain damage and neurodegeneration. Inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 279 publications
(445 reference statements)
0
37
0
Order By: Relevance
“…Neuroinflammation is a tissue response mediated by the neural cells, NPs, and yet unidentified mediators. It is involved in the development of NA [ 29 , 72 , 73 ] by inducing the hyperplasia of the neuroendocrine cells and the proliferation of the nerve fibers. These lead to an enhanced release of NPs in the wall of the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is a tissue response mediated by the neural cells, NPs, and yet unidentified mediators. It is involved in the development of NA [ 29 , 72 , 73 ] by inducing the hyperplasia of the neuroendocrine cells and the proliferation of the nerve fibers. These lead to an enhanced release of NPs in the wall of the appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived secondary metabolites with strong antioxidant capacities can reduce the prevalence of age-related neurological disorders associated with increased inflammation [ 146 , 147 ]. In vitro and in vivo experiments have shown that, by attenuating the expression of pro-inflammatory cytokines and inflammatory mediators, including tumour necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β, preventing inflammasome formation, or inducing the expression of neuroprotective anti-inflammatory and antioxidant molecules, α- and β-asarone can exert neuroprotective effects in various neurological disorders [ 78 , 82 ] ( Figure 2 ).…”
Section: Neuroprotective Effects Of α- and β-Asaronementioning
confidence: 99%
“…Primary trauma leads to structural destruction of vital organs, including cell membrane disruption, myelin and axon destruction, as well as neurovascular injury, which further triggers secondary injuries [29]. Specifically, the activation of astrocytes and microglia in the neuroinflammation process involves a complex mechanism of secondary damage to the CNS [30,31]. In a mouse model of TBI, damage-triggered changes in astrocyte morphology have been shown to be accompanied by alternative localization and aggregation of γ-synuclein, indicating potential neurodegenerative changes following CNS injuries [32].…”
Section: Traumatic Cns Injuriesmentioning
confidence: 99%